HIDING IN PLAIN SIGHT: ANTI-NMDAR- ENCEPHALITIS IN A 30-YEAR-OLD MALE- A CASE REPORT - Saeed, Muhammad Luqman; Rehman, Aisha; Naeem, Awais; Naim, Fahad (Journal of Postgraduate Medical Institute, 2023)
The most common type of autoimmune encephalitis is anti-NMDAR-encephalitis. It is characterized by IgG antibodies against the GluN1 subunit of the NMDA receptor, leading to marked neuropsychiatric and behavioural symptoms that progress in a subacute manner to seizures, speech abnormalities, and a depressed level of consciousness. In this case report, the clinical course of a 30-year-old man who first received treatment for viral encephalitis after exhibiting normal symptoms is described. CSF showed lymphocytic pleocytosis with normal brain imaging. The EEG demonstrated diffuse slowing and encephalopathy. An autoimmunity encephalitis workup was done after exhaustive investigations for metabolic and infectious causes came back negative. A diagnosis of anti-NMDAR encephalitis was made after antibodies were found in the CSF.